Desain Modul Pembelajaran Mandiri Tentang Gerak Parabola Pada Bidang Miring Tanpa Gesekan Udara - Beta Sugesti Situmeang; Debora Natalia Sudjito; Nur Aji Wibowo (Radiasi : Jurnal Berkala Pendidikan Fisika, 2019)
Generally, the learning about projectile motion on inclined surface neglecting air friction can not be delivered during the meeting hours because of the limited time. One way that can be done is by doing independent learning about projectile motion on inclined surface neglecting air friction which is assisted by an independent learning module. The purpose of this study is to design an independent learning module of projectile motion on inclined surface neglecting air friction and to investigate the effectiveness of the module toward undergraduate students’ understanding. Hopefully, this module can enrich the mechanic's modules for the undergraduate students and support them in learning about projectile motion on the inclined surface out of the meeting hours so that they can learn about the projectile motion comprehensively. The method of this study is the ADDIE model of development method consisting of Analysis, Design, Development, Implementation, and Evaluation steps. This independent learning module is applied to three freshmen of the Physics and Physics Education Department. Based on the observation sheet, the undergraduate students were able to do 88% of the module correctly, they also give 90% positive response to the statements of the module, and gets an average evaluation score of 75. Therefore, this independent learning module about projectile motion on inclined surface neglecting air friction is effective in assisting undergraduate students to understand the projectile motion on inclined surface neglecting air friction material.